PENGARUH MOTIVASI DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI PADA BALAI WILAYAH SUNGAI KALIMANTAN III DI MARINDA - -, Mahardini Octaviana (EKONOMIA, 2014)
The problem in this study is whether the motivation and leadership factors significantly influence the Employee Performance Hall Borneo River Region III, while the purpose of this study was to determine the effect of Motivation And Leadership On Employee Performance Against Hall Borneo River Region III. The usefulness of this study can be used an input for further research and for the evaluation of input and agencies in order to improve employee performanceBasic theory used is Human Resource Management by using multiple linear regression analysis with 50 samples.Conclusion peneitian this:Taken together Motivation and Leadership variables have a significant impact on employee performance on Borneo River Region III Hall. Thus the hypothesis is accepted.Partially show motivation variable (X1) sifnifikan has influence on employee performance on Borneo River Region III Hall (Y) which is indicated by the results of the calculation of the value t> t table and significance 0.000 <0.05 so the hypothesis is acceptedPartially show leadership variable (X2) sifnifikan has influence on employee performance on Borneo River Region III Hall (Y). Thus the research hypothesis is acceptedPartially indicates that the variable beta coeficient of standadrize Motivation <of beta coeficient standardize variable means variable Leadership Leadership dominant effect on the motivation variable than employee performance on Borneo River Region III Hall, thus the hypothesis that motivational factors allegedly dominant influence on employee performance in the Hall Borneo River Region III, denied